Circadian rhythmicity of synapses in mouse somatosensory cortex. (16th September 2015) - Jasinska, Malgorzata; Grzegorczyk, Anna; Woznicka, Olga; Jasek, Ewa; Kossut, Malgorzata; Barbacka‐Surowiak, Grazyna; Litwin, Jan A.; Pyza, Elzbieta; Silver, Rae
Abstract The circadian rhythmicity displayed by motor behavior of mice: activity at night and rest during the day; and the associated changes in the sensory input are reflected by cyclic synaptic plasticity in the whisker representations located in the somatosensory (barrel) cortex. It was not clear whether diurnal rhythmic changes in synapse density previously observed in the barrel cortex resulted from changes in the activity of the animals, from daily light/dark (LD) rhythm or are driven by an endogenous clock. These changes were investigated in the barrel cortex of C57BL/6 mouse strain kept under LD 12 : 12 h conditions and in constant darkness (DD). Stereological analysis of serial electron microscopic sections was used to assess numerical density of synapses. In mice kept under LD conditions, the total density of synapses and the density of excitatory synapses located on dendritic spines was higher during the light period (rest phase). In contrast, the density of inhibitory synapses located on dendritic spines increased during the dark period (activity phase). Under DD conditions, the upregulation of the inhibitory synapses during the activity phase was retained, but the cyclic changes in the density of excitatory synapses were not observed. The results show that the circadian plasticity concerns only synapses located on spines (and not those on dendritic shafts), and that excitatory and inhibitory synapses are differently regulated during the 24 h cycle: the excitatory synapses are influenced by light, whilst the inhibitory synapses are driven by the endogenous circadian clock.